2020
DOI: 10.3390/cryst10050363
|View full text |Cite
|
Sign up to set email alerts
|

Large Area Free-Standing Single Crystalline Films of p-Quinquephenyl: Growth, Structure and Photoluminescence Properties

Abstract: Studies of the growth of large-area free-standing single-crystalline films of p-quinquephenyl are presented. High-quality crystals were grown by slow cooling of a hot chlorobenzene solution. Worse quality large-area free-standing single crystals of p-quinquephenyl were also grown by using physical vapor transport and used for comparison. The crystal structure of p-quinquephenyl at 293 K and 85 K was refined by single-crystal X-ray diffraction. The optical absorption and photoluminescence spectra of solutions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The contribution of these molecules to the absorption spectrum is small, since the concentration of dislocations in crystals obtained by sublimation is usually small (Lisovenko et al, 1975). Similar phenomena were observed for p-quinquephenyl (Postnikov et al, 2020b).…”
Section: Absorption and Fluorescence Spectrasupporting
confidence: 61%
See 2 more Smart Citations
“…The contribution of these molecules to the absorption spectrum is small, since the concentration of dislocations in crystals obtained by sublimation is usually small (Lisovenko et al, 1975). Similar phenomena were observed for p-quinquephenyl (Postnikov et al, 2020b).…”
Section: Absorption and Fluorescence Spectrasupporting
confidence: 61%
“…Due to the very low solubility the method of physical vapor transport (PVT) (Laudise et al, 1998;Postnikov et al, 2020b) was applied for the growth of BTD(PO) 2 crystals. The inner diameter of the growth quartz tube was 19 mm.…”
Section: Crystal Growth and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The PVT system for growing crystals in a gradient temperature field was designed according to the classical scheme [17,24] and was used in the first stage of growth studies. A mixture of argon with 5% hydrogen (purity 99.9999%) was used as the carrier gas during crystal growth.…”
Section: Crystal Growth and Analysismentioning
confidence: 99%
“…This area of research is important for both fundamental and applied problems related to organic electronics. While classic setups with a gradient thermal field are more commonly used [17,24], some growth setups with several temperature zones forming a stepped thermal field profile have been explored in the literature. In particular, some studies have reported success in obtaining centimeter-scale organic semiconductor crystals using a PVT setup with two temperature zones [25][26][27][28], which allows for more precise control over the temperature field inside the growth tube compared to the gradient method.…”
Section: Introductionmentioning
confidence: 99%